Wildfire smoke impacts on indoor air quality assessed using crowdsourced data in California - Liang, Yutong; Sengupta, Deep; Campmier, Mark J; Lunderberg, David M; Apte, Joshua S; Goldstein, Allen H (Proceedings of the National Academy of Sciences - PNAS, 2021)
Wildfires have become an important source of particulate matter (PM < 2.5-µm diameter), leading to unhealthy air quality index occurrences in the western United States. Since people mainly shelter indoors during wildfire smoke events, the infiltration of wildfire PM into indoor environments is a key determinant of human exposure and is potentially controllable with appropriate awareness, infrastructure investment, and public education. Using time-resolved observations outside and inside more than 1,400 buildings from the crowdsourced PurpleAir sensor network in California, we found that the geometric mean infiltration ratios (indoor PM of outdoor origin/outdoor PM ) were reduced from 0.4 during non-fire days to 0.2 during wildfire days. Even with reduced infiltration, the mean indoor concentration of PM nearly tripled during wildfire events, with a lower infiltration in newer buildings and those utilizing air conditioning or filtration.